Struktur Komunitas Zooplankton dan Fitoplankton di Isi Lambung Ikan Tongkol Komo (Euthynnus affinis) - Cindy Ayu Nofitasari; Pungky Slamet Wisnu Kusuma; Dyah Hariani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Zooplankton and phytoplankton have an ecological function as primary producers in the food chain, so they are often used as a scale for measuring water fertility. The aim of the study was to determine the community structure of zooplankton and phytoplankton in terms of the level of diversity, level of uniformity, and level of dominance in the gastric contents of the Komo Tuna (Euthynnus affinis) caught by fishermen in Lamongan Waters. Sampling of the Komo Tuna fish was carried out from the catches of fishermen in Lamongan Waters. The experimental method was through direct observation of the types of zooplankton and phytoplankton in the gastric contents of the Komo Tuna fish. Analysis of zooplankton and phytoplankton community structure data in the stomach contents of the Tuna Tuna using the diversity index, uniformity index, and dominance index approaches. The results showed that the community structure of zooplankton and phytoplankton that had been identified in the gastric contents of the Tuna Tuna was in accordance with life in Lamongan waters indicated by the diversity index value belonging to the medium and low categories, the uniformity index value belonging to the high category, and the dominance index value belonging to the unstable and stable category.